Humanitarian Hypocrisy : Civilian Protection and the Design of Peace Operations. - Everett, Andrea L. (Cornell University Press, 2018)
In Humanitarian Hypocrisy, Andrea L. Everett maps the often glaring differences between declared ambitions to protect civilians in conflict zones and the resources committed for doing so. Examining how powerful governments contribute to peace ...